Reputational concerns, not altruism, motivate restraint when gambling with other people's money - Arfer, Kodi B.; Bixter, Michael T.; Luhmann, Christian C. (Frontiers in Psychology, 2015)
People may behave prosocially not only because they value the welfare of others, but also to protect their own reputation. We examined the separate roles of altruism and reputational concerns in moral-hazard gambling tasks, which allowed subjects to gamble with a partner's money. In Study 1, subjects who were told that their partner would see their choices were more prosocial. In Study 2, subjects were more prosocial to a single partner when their choices were transparent than when their choices were attributed to a third party. We conclude that reputational concerns are a key restraint on selfish exploitation under moral hazard.